Iberian Southwest Middle Bronze Age Reading social complexity in greenstone beads from the cist necropolis of Sines - Odriozola, Carlos (2016)
The results of chemical and mineralogical analysis of a set of greenstone beads from the Middle Bronze Age cemeteries of Provença and Pessegueiro in the region of Sines (southwest Portuguese coast) showed that these adornments were not made out of variscite, but of raw material available in the geological structure of Serra do Cercal. The regional scarcity of this type of artefacts and its association with gold and silver grave goods in the most qualified burials of both cemeteries allows an inquiry on material expressions of social complexity in the Bronze Age of the southwest of the Iberian Peninsula.